The national Swedish value of time study - Algers, Staffan; Dillén, Johanna Lindquist; Wildert, Staffan (Proceedings from the Annual Transport Conference at Aalborg University, 1995)
In Sweden, cost benefit evaluations have been part of the planning process for many years. In these cost benefit evaluations, the value of time plays an important role. This project aims at providing VoT’s for new guidelines for project evaluation. A more general aim of the study is to provide more insight in VoT issues, especially for business trips. The Hensher formula was used for calculation of the VoT’s for business trips. But as the aim was to look deeper into business trips, it was decided to extract samples also for behaviour values and for the group of self-employed persons. The project was carried out in Sweden 1994/95. It is concentrated to regional and long distance trips, since they will be the most important trip types in the evaluation work. Approximately 5000 interviews were completed.